Case report: Treatable immune-mediated severe orthostatic hypotension in SARS-CoV-2 infection - Theiler, Kenji; Bronchain, Maroussia; Grouzmann, Eric; Duflon, Serge; Hirt, Lorenz; Du Pasquier, Renaud; Waeber, Gérard; Wuerzner, Grégoire; Diserens, Karin; Bally, Julien F. (Frontiers in Neuroscience, 2025)
We report a patient with autonomic dysfunction following acute SARS-CoV-2 infection, presenting progressively worsening severe orthostatic hypotension to the point where she could no longer sit or stand. The patient experienced a delay in diagnosis after an initial misdiagnosis of a functional neurological disorder. Persistent orthostatic symptoms prompted us to re-examine the diagnosis and explore other diagnostic tools, which ultimately allowed us to identify and treat severe immune-mediated orthostatic hypotension (OH). We identified autoantibodies (AAB) targeting the autonomic nervous system. Intravascular immunoglobulin therapy, along with early, specific multi-disciplinary rehabilitation, completely resolved the symptoms. Hard-to-assess patients are often penalized by suboptimal care due to the lack of a comprehensive patient history and physical examination, resulting in unnecessary and costly ancillary examinations that lead to delays in diagnosis or misdiagnoses. Furthermore, a lack of awareness of rare complications with new diseases may also hamper proper patient care. In the present case, this includes the wide range of SARS-CoV-2 infection manifestations, including immune-mediated autonomic complications.